THE EFFECTS OF ADSORBENT MASS USING RED BRICK POWDER ON THE RESULTS OF BIOGAS PURIFICATION - Wahyudi, Slamet; Nurahmad Efendi, Firman; Faizal, Ahmat (Journal of Applied Engineering Science, 2020)
Biogas is produced by the digestion of organic waste by anaerobic bacteria. However, the application of raw biogas is not effective because it consists of impurities such as carbon dioxide (CO2), hydrogen sulfide (H2S), water vapor (H2O), and other impurity gases. Physical Adsorption is the simplest method of immobilization of biomolecules such as CO2 which is attached to the surface through the weak bonds like van der Waals forces. One of the physical adsorption means to reduce CO2 levels in biogas is to use brick powder. Increasing of brick powder adsorbent mass caused the decrease of CO2 concentration in the biogas purification. Brick is a porous material containing SiO2Al2O3, so it has the ability to form Van Der Waals bonding forces with CO2. The goal of this research is to determine the efficiency of brick powder as a purification adsorbent to reduce of CO2 levels using the 23 factorial design method.The application of 200 and 400 grams brick powder adsorbents, with the biogas flow rate of 1 and 2 liters/minute, was researched at intervals of 5 and 20 minutes, for the CO2 concentration data and heating values of biogas. Gas Chromatography (GC) was used to determine the concentration of adsorption gases, especially CO2 and CH4. The results showed that the biggest efficiency reduction in CO2 concentration is 59.28 %.